1993
DOI: 10.1037/0033-295x.100.2.347
|View full text |Cite
|
Sign up to set email alerts
|

What is important about McCollough effects? Reply to Allan and Siegel.

Abstract: Criticism of the authors' functional theory of the McCollough effect (ME) is answered. The critics claim that MEs can be explained as classical conditioning effects. It is not disputed that the association-forming process in MEs shares much in common with classical conditioning, but there are still problems, practical and theoretical, with this account. It also misdirects attention from more important matters. The role of MEs in assuring a proper fit between representation and environment is reasserted, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Thus, as causes and effects are expected to correlate, detecting these relationships, or contingencies, is a valuable skill to infer potential causality. In line with this reasoning, a great corpus of experimental evidence strongly suggests that manipulations of the contingency between potential causes and effects produce the corresponding variations in people’s judgments of causality ( Allan and Jenkins, 1980 ; Shanks and Dickinson, 1987 ; Dodwell and Humphrey, 1993 ; Blanco et al, 2010 ).…”
Section: Introductionmentioning
confidence: 87%
“…Thus, as causes and effects are expected to correlate, detecting these relationships, or contingencies, is a valuable skill to infer potential causality. In line with this reasoning, a great corpus of experimental evidence strongly suggests that manipulations of the contingency between potential causes and effects produce the corresponding variations in people’s judgments of causality ( Allan and Jenkins, 1980 ; Shanks and Dickinson, 1987 ; Dodwell and Humphrey, 1993 ; Blanco et al, 2010 ).…”
Section: Introductionmentioning
confidence: 87%
“…Its application to such phenomena has not been without criticism. For example, Dodwell and Humphrey (1993) suggested that Allan and Siegel's (1993) application of the RescorlaWagner model to the McCollough effect "attempts to divert modeling to a different direction from the one we find most insightful, not to say compelling" (p. 347). Markovits and Dumas (1992) took exception to Fersen et al's (1991) associative analysis of transitive inference in pigeons: "Great care must be taken before it is possible 'to unambiguously equate complex cognitive abilities with simple information-processing mechanisms" (p. 312).…”
Section: Resultsmentioning
confidence: 99%
“…As a result ofthe pairing ofthe CS (lined grid) with the DCS (color) a conditioned response (CR) develops so that the adaptive response of the visual system to the color is evoked by the lined grid" (p. 615). There has been considerable controversy about the value of interpreting the McCollough effect as an instance of classical conditioning (see, e.g., Allan & Siegel, 1986;Dodwell & Humphrey, 1993;Skowbo, 1984), but there have been many reports supporting this associative analysis of the phenomenon (e.g., Brand, Holding, & Jones, 1987;Eissenberg, Allan, Siegel, & Petrov, 1995;Siegel, Allan, & Eissenberg, 1992;Westbrook & Harrison, 1984). Many of the experiments evaluating the conditioning interpretation of the McCollough effect have been inspired by the Rescorla-Wagner model.…”
Section: Perceptionmentioning
confidence: 99%
“…If, however, the test patterns are rotated 450 from the adapted orientations, colour aftereffects are not reported. Since McCollough's original report, numerous studies of this aftereffect have confirmed and extended her initial findings (for reviews see [2][3][4]), and several accounts of its functional role in vision have been proposed [2,[5][6][7]. One of the issues that has concerned researchers is the locus in the visual system of the mechanisms that mediate the effect.…”
Section: Introductionmentioning
confidence: 91%